GABA-B receptors in the PNS have a role in Schwann cells differentiation? - Procacci, Patrizia; Ballabio, Marinella; Castelnovo, Luca F.; Mantovani, Cristina M.; Magnaghi, Valerio (Frontiers in Cellular Neuroscience, 2013)
GABA-B receptor mediates the inhibitory transmission of -aminobutyric acid in the mammalian nervous system, being present in neurons and also in glial cells. Recently the presence of GABA-B has been demonstrated in Schwann cells suggesting its contribution in regulating the cell fate, maturation and plasticity. Here, we further support the functional presence of GABA-B receptor in Schwann cells plasma membrane. By confocal microscopy immunofluorescence we provide evidences that GABA-B localization on the cell elongated processes correlates with the morphological changes occurring in the differentiated Schwann cells. In vivo most of the GABA-B receptors seem to be present in non-myelinating Schwann cells, which are committed to en-sheet the nociceptive fibers. Therefore, we argue that GABA-B receptors do not control exclusively the in vivo differentiation yielding the myelinating Schwann cells, but are also fundamental in regulating the Schwann cells plasticity versus the non-myelinating state. Data from the literature and our recent findings corroborate the role of the GABAergic system and GABA-B receptors in the peripheral nervous system, opening new perspectives on the mechanisms controlling the differentiation of Schwann cells